Perancangan Video Pembelajaran Animasi 2D Pengenalan Kosa Kata Bahasa Inggris Hewan dan Buah - Wisnu Aji; Lilik Sugiarto; Hadis Turmudi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Learning videos are a medium or tool used in the educational process to convey information, concepts or learning materials to students using visual and audio elements. The purpose of this design is to create a teaching and learning activity that is fun and effective. Making this learning media uses Adobe Illustrator software as an asset maker, and Adobe After Effects to create the animation. This learning video design uses the ADDIE method. Then to collect data using a questionnaire with 6 question indicators, from the 6 question indicators the score was 90.9%, it can be concluded that this learning video can be said to be successful and capable of being an alternative in teaching and learning activities at Pertiwi Mundu Kindergarten, Klaten, Central Java. This learning video contains 10 names of fruit, 10 names of animals taken from the surrounding environment, this design aims to enable children to fish and know English in everyday life.